Development and validation of a novel high-performance liquid chromatography (HPLC) method for the detection of related substances of pralsetinib, a new anti-lung cancer drug - Zhu, Yonghong; Qin, Jisu; Wu, Wenyi; Cai, Liangliang (Frontiers in Chemistry, 2024)
Background Pralsetinib, a targeted inhibitor of the RET enzyme, plays a critical role in the treatment of adult patients with locally advanced or metastatic non-small cell lung cancer (NSCLC) characterized by RET gene fusion mutations following platinum-based chemotherapy. Nevertheless, impurities resulting from the manufacturing and degradation of pralsetinib have the potential to impact its therapeutic effectiveness and safety profile. Methods To address this issue, a liquid chromatography method was developed and validated for the specific identification of pralsetinib and its related impurities. The separation of pralsetinib and its related impurities was achieved via a Waters X Bridge C18 column with dimensions of 4.6 mm × 250 mm and a particle size of 5 μm. Mobile phase A was composed of 20 mmol/L potassium dihydrogen phosphate (KH2PO4) and acetonitrile (ACN) at a volume ratio of 19:1, while mobile phase B consisted solely of ACN, utilizing a gradient elution technique. Detection was performed at a wavelength of 260 nm, with an injection volume of 10 μL and a flow rate of 1.0 mL/min. Results The chromatographic method established in this study was validated according to the ICH Q2 (R1) guidelines. The method demonstrated excellent linearity over a specific concentration range (imp-A: 0.035–10.21 μg/mL; imp-B: 0.09–10.16 μg/mL; imp-C: 0.15–10.19 μg/mL; pralsetinib: 0.04–10.32 μg/mL). Additionally, the method possesses high sensitivity, with detection limits for impurities A, B, C, and pralsetinib of 0.01, 0.03, 0.015, and 0.013 μg/mL, respectively, and quantification limits of 0.035, 0.09, 0.05, and 0.04 μg/mL, respectively. In terms of specificity, stability, repeatability, accuracy, and robustness, the method met the validation acceptance criteria. Overall, the chromatographic technique established in this study can effectively separate pralsetinib and its impurities, providing reliable assurance for the accurate detection and quantification of impurities. Conclusion The chromatographic method developed in this study can be utilized for the detection of pralsetinib and its impurities, offering a crucial reference for research on the quality of pralsetinib.